2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-1.12432
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent cytotoxicity of dichloroacetate and metformin against Lewis lung carcinoma

Abstract: Summary. The use of inhibitors of energy metabolism of malignant cells is a new promising trend in the treatment of cancer patients, based on one of the unique features of the malignant cell, namely the dominance of glycolysis over oxidative phosphorylation, even in the presence of oxygen, the so-called Warburg effect. Aim: To study time-dependent cytotoxicity of sodium dichloroacetate (DCA) and metformin (MTF) against metastatic tumor cells and action of these agents on tumor cell migration. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Similar results were obtained in melanoma cells in which the administration of retinoic acid receptor β (RAR β ) inhibitors confer sensitization to DCA [41]. A positive effect of DCA coadministration with metformin, a hypoglycaemic drug widely used to treat diabetes was demonstrated in a preclinical model of glioma [42] as well as in a low metastatic variant of Lewis lung carcinoma (LLC) [43]. Jiang and colleagues investigated the effects of phenformin, a metformin analog, and DCA in glioblastoma, demonstrating that contemporary inhibition of complex I and PDK by phenformin and DCA, respectively, decreased self-renewal and viability of glioma stem cells (GSCs), thus suggesting their possible employment to affect cancer stem cell fraction [44].…”
Section: Synergistic Effect Of Dca and Other Potential Anticancer mentioning
confidence: 63%
“…Similar results were obtained in melanoma cells in which the administration of retinoic acid receptor β (RAR β ) inhibitors confer sensitization to DCA [41]. A positive effect of DCA coadministration with metformin, a hypoglycaemic drug widely used to treat diabetes was demonstrated in a preclinical model of glioma [42] as well as in a low metastatic variant of Lewis lung carcinoma (LLC) [43]. Jiang and colleagues investigated the effects of phenformin, a metformin analog, and DCA in glioblastoma, demonstrating that contemporary inhibition of complex I and PDK by phenformin and DCA, respectively, decreased self-renewal and viability of glioma stem cells (GSCs), thus suggesting their possible employment to affect cancer stem cell fraction [44].…”
Section: Synergistic Effect Of Dca and Other Potential Anticancer mentioning
confidence: 63%
“…• DCA targets mainly cells that cannot use the oxidative metabolism 248 . This concept is further confirmed by the synergy between DCA and metformin [267][268][269][270][271][272][273][274] . The fundamentals of this association stem from the fact that metformin inhibits mitochondrial Complex I and reduces oxidative metabolism while DCA inhibits glycolysis.…”
Section: Treatment Proposalmentioning
confidence: 87%
“…To reduce the required DCA dose and associated side effects and to avoid resistance development, the combination therapy with a synergistic substance is a promising approach in cancer therapy [ 55 ]. In vitro studies demonstrated a synergistic effect of DCA and metformin in human breast cancer cells [ 13 ], human ovarian cancer cells [ 14 ], Lewis lung carcinoma [ 56 ], and murine glioblastoma cells [ 15 ]. Both substances are easy to synthesize and metformin is already approved as therapeutic for human medicine [ 56 , 57 ], while DCA has been used in humans for the treating lactic acidosis [ 24 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%